ЦИФРОВЫЕ ФИНАНСОВЫЕ ТЕХНОЛОГИИ КАК ФАКТОР ПРИВЛЕЧЕНИЯ КАПИТАЛА ЧАСТНЫМИ КОМПАНИЯМИ НА МЕЖДУНАРОДНЫХ РЫНКАХ - Турдымуратова Азиза Кыясовна, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract. This article examines a number of studies devoted to digital financial technologies  (FinTech)  as  a  tool  for  attracting  capital  by  private  companies  in international markets. Proposals are presented on the use of modern technologies to reduce the costs of raising financing, expand access to global investors, and increase the transparency of financial transactions. Particular attention is paid to the impact of digitalization on the efficiency of interaction with foreign investors and the reduction of risks in international financing.